Spiders in apple orchards in Valtellina (Arachnida, Araneae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The research aimed at improving the knowledge of natural predators in agroecosystems under cultivation and in particular of Spiders. Three apple orchards of different age situated in the fruit area of Valtellina (province of Sondrio) and formerly studied as to their Carabids and Chilopods populations, from January to December 1990 some pitfall traps were set 682 samples of spiders, belonging to 36 species of 13 different families, were captured: 2 species were signalled for the first time in Italy and 11 in Lombardy. The studied apple orchards, chemically treated with fungicides and insecticides, turned out to be rather rich in spiders but poorer if compared with the data obtained by pieces of biotopes where the fitosanitary interventions were absent. It came out that it would be necessary to supply the edges of such intensive agroecosystems with elements such as hedges, rows of trees and groves able to give shelter and protection to the many natural elements of phytofagy, and therefore in particular to Spiders.
Keywords: appie orchards; agroecosystems; spiders; Valtellina